Diagnostic pitfalls in vitamin B6‐dependent epilepsy caused by mutations in the PLPBP gene. Issue 1 (30th September 2019) - Jensen, Kristian Vestergaard; Frid, Maria; Stödberg, Tommy; Barbaro, Michela; Wedell, Anna; Christensen, Mette; Bak, Mads; Ek, Jakob; Madsen, Camilla Gøbel; Darin, Niklas; Grønborg, Sabine
Abstract: Vitamin B6‐responsive epilepsies are a group of genetic disorders including ALDH7A1 deficiency, PNPO deficiency, and others, usually causing neonatal onset seizures resistant to treatment with common antiepileptic drugs. Recently, biallelic mutations in PLPBP were shown to be a novel cause of vitamin B6‐dependent epilepsy with a variable phenotype. The different vitamin B6‐responsive epilepsies can be detected and distinguished by their respective biomarkers and genetic analysis. Unfortunately, metabolic biomarkers for early detection and prognosis of PLPBP deficiency are currently still lacking. Here, we present data from two further patients with vitamin B6‐dependent seizures caused by variants in PLPBP, including a novel missense variant, and compare their genotype and phenotypic presentation to previously described cases. Hyperglycinemia and hyperlactatemia are the most consistently observed biochemical abnormalities in pyridoxal phosphate homeostasis protein (PLPHP) deficient patients and were present in both patients in this report within the first days of life. Lactic acidemia, the neuroradiological, and clinical presentation led to misdiagnosis of a mitochondrial encephalopathy in two previously published cases with an early fatal course. Similarly, on the background of glycine elevation in plasma, glycine encephalopathy was wrongly adopted as diagnosis for a patient in our report. In this regard, lactic acidemia as well as hyperglycinemia appear to be diagnostic pitfalls in patients with vitamin B6‐responsive epilepsies, including PLPHP deficiency. Synopsis: In vitamin B6‐responsive epilepsies, including PLPHP deficiency, there are several diagnostic pitfalls, including lactic acidemia as well as hyperglycinemia, highlighting the importance of a pyridoxine trial, and genetic testing.